Kadar Zat Besi dan Uji Hedonik pada Cookies Berbahan Tepung Kelakai dan Kacang Hijau - Lamia Diang Mahalia; Grace Abigail Larongge; Harlyanti Muthmaâ€™innah Mashar (LPPM Universitas Abdurrab, 2024)
Background: To promote local food security, food diversification efforts can be made by utilizing local food sources such as kelakai and mung beans that can be processed into flour as a substitute for wheat flour in making cookies. Objectives: Analyze the iron content and determine the characteristics, organoleptic quality, and acceptability of cookies made from kelakai bean flour and mung bean flour. Methods: Completely Randomized Design with 3 treatments, F1 with a ratio of 40 g mung bean flour and 10 g kelakai flour, F2=40 g : 15 g, and F3=40 g: 20 g. Characteristics and acceptability testing using hedonic test; Fe content using atomic absorption spectophotometry. Results: The cookies produced have the characteristics of brownish green color, unpleasant odor (langu), less sweet taste, and very crunchy texture. The largest Fe content is in formula F3 which is 1.305 mg per piece of cookies (Â± 45 grams). The results of the acceptability test on aroma, taste, color, and texture show that the most preferred cookies are in formula F1. Conclusion: Cookies formula F1 has the potential to be developed into functional food because it has a fairly high iron content and good acceptability.